Laporan Kasus: Epilepsi pada Wanita Muda: Cases Report: Epilepsy in Young Woman - Noviyanty Indjar Gama; Dinda Tri Rahayu; Fridya Maulitha; Novia Anggriani; Rizky Mulyaramadhan; Zulianita Zulianita; Falda Gizella Mangnga; Ratna Aprilia Sari; Yuliana Megi Pasudi (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Epilepsy is a chronic disorder of the brain characterized by recurrent seizures caused by excessive electrical discharges in a group of nerve cells. Epilepsy is one of the causes of morbidity that can attack all ages. This disease can reduce the quality of life for sufferers. It estimated that around 50 million people suffer from epilepsy in the world, and 80% of the total sufferers come from developing countries. Seizures occur due to excessive excitation or due to irregular inhibition of neurons. This case report concerns female epileptic patient (14 year old) in outpatient treatment. The patient received anti-epileptic drug therapy (AED), namely Depakote, Folic Acid and Kutoin. The therapy had given can control the patient's seizure condition for three years without any side effects or adverse drug reactions. Keywords: Epilepsy, Management, Anti-Epileptic Drugs (AED) Abstrak Epilepsi adalah kelainan kronis pada otak yang ditandai dengan kejang berulang akibat pelepasan muatan listrik yang berlebihan pada sekelompok sel saraf. Epilepsi menjadi salah satu penyebab morbiditas yang dapat menyerang semua umur. Penyakit ini dapat menurunkan kualitas hidup bagi penderita. Diduga terdapat sekitar 50 juta orang menderita epilepsi didunia, dan 80% dari total penderita berasal dari negara berkembang. Kejang terjadi akibat eksitasi yang berlebihan atau akibat penghambatan neuron yang tidak teratur. Laporan kasus ini mengenai kejadian epilepsi pada pasien wanita berusia 14 tahun di pengobatan rawat jalan. Pasien mendapatkan terapi obat anti epilepsi (OAE) yaitu Depakote, Asam Folat dan Kutoin. Terapi yang diberikan dapat mengendalikan kondisi kejang pasien selama 3 tahun tanpa adanya efek samping atau reaksi obat yang merugikan. Kata Kunci: Epilepsi, Tatalaksana, Obat Anti Epilepsi (OAE)